ORGANIC SULFUR COMPOUNDS FORMED DURING EARLY DIAGENESIS IN BLACK SEA SEDIMENTS - Wakeham S.G.; Sinninghe Damste J.S.; Kohnen M.E.L.; De Leeuw J.W. (My University, 1995)
Sediments from Units I and II of the Black Sea were analyzed to assess the early diagenetic formation of organic sulfur compounds (OSC). A series of isomeric C28-2,4-dialkylthiophenes was found at low concentrations in surface sediments. OSC with C25-highly branched isoprenoid (HBI) skeletons were not found in surface sediments even though there was a rapid decrease in the concentrations of C25-HBI alkenes in the same sediments, nor were OSC found which contained carbon skeletons derived from C37-C39 alkenes which are also abundant in the sediment. As depth increased in Unit I, concentrations of the C28-2,4-dialkylthiophenes decreased while C25- and C30-HBI thiolanes appeared at the bottom of Unit I and increased in concentration into Unit II. Treatment of macromolecular material from sediment extracts with Raney nickel yielded phytane as the dominant hydrocarbon as well as series of C25- and C30-HBI hydrocarbons, β-carotane, and isorenieratane. These latter two components were generally absent from the free hydrocarbon fractions. These results indicate that sulfur incorporation into functionalized lipids can occur during the very early stages of sedimentary diagenesis, even at the sediment-water interface. On the other hand, the rapid loss of C25-HBI alkenes in surface sediments could not be accounted for by sulfur quenching, and other potential OSC-precursors, such as C37-C39 alkenes, also apparently did not incorporate sulfur into readily-analyzable material.